Natural Bioactive Molecules as Potential Agents Against SARS-CoV-2 - Chen, Wei; Wang, Zhihao; Wang, Yawen; Li, Yiping (Frontiers in Pharmacology, 2021)
In the past two decades, pandemics of several fatal coronaviruses have posed enormous challenges for public health, including SARS-CoV (2003), MERS-CoV (2012), and SARS-CoV-2 (2019). Among these, SARS-CoV-2 continues to ravage the world today and has lead to millions of deaths and incalculable economic damage. Till now, there is no clinically proven antiviral drug available for SARS-CoV-2. However, the bioactive molecules of natural origin, especially medicinal plants, have been proven to be potential resources in the treatment of SARS-CoV-2, acting at different stages of the viral life cycle and targeting different viral or host proteins, such as PLpro, 3CLpro, RdRp, helicase, spike, ACE2, and TMPRSS2. They provide a viable strategy to develop therapeutic agents. This review presents fundamental biological information on SARS-CoV-2, including the viral biological characteristics and invasion mechanisms. It also summarizes the reported natural bioactive molecules with anti-coronavirus properties, arranged by their different targets in the life cycle of viral infection of human cells, and discusses the prospects of these bioactive molecules for the treatment of COVID-19.